Some Integrals Pertaining Biorthogonal Polynomials and Certain Product of Special Functions (Global Journal of Science Frontier Research, 2012)
The main object of this paper is to obtain some integrals and series relation pertaining to biorthogonal polynomials, Fox's H-function, the general class of polynomials and the Hfunction of several complex variables.
Keywords: Foxs H-function; the general class of polynomials and the H-function of complex variables